DIGITAL TRANSFORMATION OF SMEs IN KEDIRI: THE IMPACT OF QRIS ADOPTION - Saputro, Rico Edi; Retnasih, Nora Ria (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
This research aims to analyze the implementation of QRIS as an electronic payment method for MSMEs in Kediri City to encourage economic growth in the era of digitalization. Using face-to-face interviews with randomly selected respondents, this research involved 6 respondents who were divided equally into two groups, namely 3 business stakeholders who had implemented QRIS and 3 stakeholders who were business actors who had not implemented QRIS. The research results show that QRIS brings several significant benefits for MSMEs, including increased income, customer satisfaction, transaction security, and better financial management. However, the spread of QRIS in Kediri has not been evenly distributed due to a lack of understanding, dependence on traditional payment methods, doubts about how QRIS works, and security issues. This research also shows that social influences from family and environment play an important role in customers' interest in implementing QRIS. Therefore, the government's role is very important in providing adequate education and awareness as well as improving technological infrastructure to support wider QRIS adoption. With the right strategy, QRIS can be an effective tool to encourage the development of the MSME economy in Kediri City in the era of digitalization